Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/medicina58060785
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Abdominal Hypertension: A Systemic Complication of Severe Acute Pancreatitis

Abstract: Patients with severe acute pancreatitis (SAP) present complications and organ failure, which require treatment in critical care units. These extrapancreatic complications determine the clinical outcome of the disease. Intra-abdominal hypertension (IAH) deteriorates the prognosis of SAP. In this paper, relevant recent literature was reviewed, as well as the authors’ own experiences, concerning the clinical importance of IAH and its treatment in SAP. The principal observations confirmed that IAH is a frequent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…However, as for AP, the international clinical guidelines paid less attention to neostigmine despite the fact that neostigmine with or without TCM was widely used in clinical practice in the department of gastroenterology and ICUs in lots of hospitals in China for non-mild AP, especially with enteroparalysis or IAH (Tenner et al, 2013;Greenberg et al, 2016;Crockett et al, 2018a;Crockett et al, 2018b;Leppaniemi et al, 2019). We speculated that the reason was that all previous related studies were published in the Chinese language in the local journals until He et al published a high-quality RCT in an international journal in 2022 (He et al, 2022;Mancilla Asencio and Berger Fleiszig, 2022). To the best of our knowledge, this systematic review was the first review that included all RCTs with the latest review published in March, 2022, about neostigmine treatment for nonmild AP, providing strong current evidence in this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as for AP, the international clinical guidelines paid less attention to neostigmine despite the fact that neostigmine with or without TCM was widely used in clinical practice in the department of gastroenterology and ICUs in lots of hospitals in China for non-mild AP, especially with enteroparalysis or IAH (Tenner et al, 2013;Greenberg et al, 2016;Crockett et al, 2018a;Crockett et al, 2018b;Leppaniemi et al, 2019). We speculated that the reason was that all previous related studies were published in the Chinese language in the local journals until He et al published a high-quality RCT in an international journal in 2022 (He et al, 2022;Mancilla Asencio and Berger Fleiszig, 2022). To the best of our knowledge, this systematic review was the first review that included all RCTs with the latest review published in March, 2022, about neostigmine treatment for nonmild AP, providing strong current evidence in this field.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used as a prokinetic drug in the treatment of AP, especially with gut dysfunction and IAH. Several previous studies showed that it had positive effects on AP with the latest randomized controlled trials (RCTs) published in March 2022, suggesting that neostigmine could reduce IAH and promote defecation (Schneider et al, 2014;He et al, 2022;Mancilla Asencio and Berger Fleiszig, 2022). However, its clinical value for AP has remained debatable so far, and the current international clinical guidelines did not attribute enough importance to this drug.…”
Section: Introductionmentioning
confidence: 99%
“…However, its clinical effect remains unclear according to previous studies, including the latest one published in March 2022. [18][19][20] Currently, international clinical guidelines have not attached importance to this drug, and no systemic review has addressed this topic. [21][22][23][24] Therefore, this systemic review and meta-analysis aim to assess the efficacy and safety of neostigmine for the treatment of AP.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Neostigmine, as a prokinetic drug, seems to play an essential role in the treatment of AP, especially when gut dysfunction occurs. However, its clinical effect remains unclear according to previous studies, including the latest one published in March 2022 18–20. Currently, international clinical guidelines have not attached importance to this drug, and no systemic review has addressed this topic 21–24.…”
Section: Introductionmentioning
confidence: 99%
“…11 Early complications of AP, as key events of disease prognosis, are crucial for AP patients to be identified and intervened early. 12,13 However, to our knowledge, only limited clinical studies have focused on the relationship between some serological indicators (such as C-reactive protein [CRP], neutrophil-to-lymphocyte ratio [NLR], etc.) and early complications of AP, and hardly any studies have systematically evaluated the relationship between cytokine profiles and early complications of AP.…”
Section: Introductionmentioning
confidence: 99%